BIG DATA AND ITS BENEFITS AT MUHAMMADIYAH UNIVERSITY OF SOUTH TAPANULI - Lubis, Efi Amrina (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
Information is now a valuable asset that changes the pattern of life in carrying out activities. After the existence of information technology, many impacts have been felt, one of which is the method of obtaining information from large data sets. Large data sets are known as “big data”. Libraries use big data to store, organize and analyze information. The use of big data has a significant impact in the library world, especially in terms of advancing and developing the library. This encourages librarians to learn how to process, analyze and present data to support knowledge generation. This article aims to provide an overview of Big Data and its benefits in the library of Universitas Muhammadiyah Tapanuli Selatan. It is hoped that this article can provide insight for libraries to utilize the potential of Big Data.